PENGARUH PERSEPSI HARGA DAN DAYA TARIK WISATA PADA KEPUASAN PENGUJUNG DANAU SHUJI DESA LEMBAK DI MASA PANDEMI COVID 19 - Sales Seftavia; Rismansyah Rismansyah; Erdiansyah Erdiansyah (FE Program Studi Manajemen, 2021)
ABSTRAKThis study was to determine the effect of price perception and tourist attraction on consumer satisfaction of Lake Shuji in Lembak Village Covid 19 pandemic. The method used in this study is a quantitative method with a sample of 109 visitors. The data analysis technique used in this research is simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test, f test using the software program spss 22 for windows.